Expression of Periostin and Identification of Periostin-Isoforms in Colorectal Carcinoma - Chia, Sze-Wooi; Sim, Edmund Ui- Hang (Malaysian Journal of Science, 2009)
Periostin, a gene that is initially associated with bone and tooth development, is linked to tumourigenesis of colorectal carcinoma (CRC). Increasing evidence via functional study revealed this protein as an oncogenic promoter or, in certain circumstances, as a tumour suppressor. Therefore, in order to verify the role of periostin in CRC, we performed gene expression study using semi-quantitative reverse transcription-polymerase chain reaction (RT-PCR) analysis in local and commercially available colorectal cancer samples. Expression of periostin mRNA was detected at a significantly higher level in the tumour specimens (P < 0.05), suggesting this gene as a putative oncogene. Further studies using PCR and gene sequencing assays revealed the presence of ten periostin isoforms that harbour deletion at specific C-terminus region, possibly caused by alternative splicing events. Three isoforms were identical to published data of periostin (GenBank), while the remaining variants that have not been reported may provide new information on the genetics of colon cancer.